Enhancing Teaching Excellence: A Review of Teacher Professional Development Strategies - Yadav, Harshita (Journal of Advanced Research in English & Education, 2024)
Teacher professional development (PD) is paramount for enhancing teaching effectiveness and improving student outcomes. This review examines various approaches to teacher PD, including traditional models, collaborative communities, technology-enabled platforms, inquiry-based practices, and mentoring programs. While traditional PD workshops offer valuable insights, their impact may be enhanced through sustained collaboration and ongoing support. Collaborative PD communities foster a sense of belonging among educators, while technology-enabled platforms facilitate flexible and accessible learning opportunities. Inquiry-based PD encourages reflective practice and experimentation, empowering teachers to drive their professional growth. Additionally, mentoring programs provide personalized support for novice teachers, contributing to increased retention rates and student achievement. By adopting a multifaceted approach to PD, education stakeholders can create a culture of continuous learning and excellence in teaching.